“From street soldiers to political soldiers”: Assessing how extreme right violence has been criminalised in Portugal - Da Silva, R.; Ventura, J. P.; Carvalho, C. M. de; Barbosa, M. R. (Critical Studies on Terrorism, 2022)
Historical evidence points to the fact that extreme right-wing (ERW) violence has not always been prosecuted under terrorism legislation, but under various other criminal statutes. In Portugal, since the regulation of terrorism in the general Criminal Code in 1982, which was then replaced by counterterrorism (CT) legislation in 2003, there have been five terrorism convictions. However, none was related to ERW violence, despite the existence of numerous ideologically motivated crimes committed by groups and individuals occupying this side of the political spectrum. In this study, we aim to understand the reasons behind such penal selectivity in contemporary Portugal by comparing two legal files: the first case sentenced according to the Portuguese CT Law, whose defendant was a Spanish national, and member of Euskadi Ta Askatasuna (ETA); and the first case of ERW violence sentenced after the introduction of the Portuguese CT Law, in which 36 alleged skinheads were sentenced for racial discrimination and incitement to hatred and violence, as expressed in section 240 of the Portuguese Criminal Code. We discuss how the Portuguese case can contribute to the international debate regarding the criminalisation of ideologically motivated violence.